A Dyadic Approach to Examining the Emotional Intelligence–Work Outcome Relationship: The Mediating Role of LMX. (2nd January 2018) - Lee, Minsu; Mayfield, Clifton O.; Hinojosa, Amanda S.; Im, Yooshin
ABSTRACT: Adopting a dyadic approach, we examine the processes through which leader–member exchange (LMX) mediates the relationship between emotional intelligence (EI) and work outcomes. Fitting the data from a survey of 204 unique pairs of leaders and followers to an actor–partner independence model (APIM), we found that follower EI positively affects LMX as perceived by both dyad members, whereas leader EI is positively related to only leader ratings of LMX. Using polynomial regression, we also found that EI similarity between the leader and follower has a positive relationship with both leader and follower ratings of LMX. Follower LMX partially mediates the relationship between follower EI and attitudinal outcomes (i.e., organizational commitment and job satisfaction) and organizational citizenship behavior. Leader LMX fully mediates the effect of both leader and follower EI on evaluations of job performance. Implications and limitations are discussed.